Elementary School Teachers' Responses in Implementing Religious Character Values Using Android-Based Learning Media - Rachmadtullah, Reza (Eduprof : Islamic Education Journal, 2022)
The use of smartphones or gadgets may be something new in the world of education. However, if you look the use of smartphones as a learning medium is very good, because students will find it easier to find learning materials is needed and can also provide opportunities and freedom for students to access wider subject matter which may not have been taught by educators.This research aims to find out how elementary school teachers respond in implementing religious characters using Android-based learning media. This research uses descriptive research methods. The results of the research, namely implementing religious characters with the help of Android-based learning media, are a concrete manifestation of current technological advances which were created to make it easier for humans to communicate and so on. This Android-based learning media is easy for teachers and students to use, and the appearance of the application on Android can attract and motivate students. Teachers also find it easy to teach examples so that religious values are easily understood by students. These application products can be downloaded on smartphones and gadgets with the Android operating system, usually available on Google Play or Play Store. Basically, Android application-based learning media is a learning media product in the form of an application that can be downloaded or downloaded on an Android-based smartphone.